Effect of the Directive and Non-directive Inspection Approaches on Teach-er Instructional Effectiveness in Government- aided Primary Schools in Nakisunga County, Uganda - Ntege, Joseph Lubwama; Kasule, Geirge Wilson; Owino, Phillip; Mugizi, Wilson (Future Science / FSH-PH Publications, 2023)
This study investigated the effect of the directive and non-directive school inspection approaches on teacher instructional effectiveness. While teacher instructional effectiveness was studied in terms of reporting on pupil academic achievements, teacher attitudes, effective planning, attendance and pedagogical approaches, the directive School inspection approach was studied in terms of directing and evaluation of teacher knowledge yet the non-directive approach was studied in terms of team planning and consultations. A cross-sectional survey mixed research design using the quantitative and qualitative approaches on a sample of 178 people namely teachers, head teachers, school inspectors and education officers was adopted. While quantitative data was collected using survey questionnaires and analysed using inferential analysis, qualitative data was collected through interviews, focus group discussions and analysed by grouping the responses in themes which were merged with quantitative findings. The findings showed that all the attributes of directive inspection approach were positively insignificant to teacher instructional effectiveness explaining that they had no impact on teacher instructional effectiveness. Similarly, team planning had a positive and insignificant relationship meaning that it had no effect on teacher instructional effectiveness. In conclusion, only team planning had effect on teacher instructional effectiveness and consultation did not have any effect. It was recommended that school inspectors should use the non-directive inspection approach because of sub-variable team planning that had a positive effect on teacher instructional effectiveness.